What Makes NPOs Sustainable in an Emergency? Examining the Effect of Person-Organization Fit and Generation on Volunteer Activities During the COVID-19 Pandemic - Choi D; Lee KH; Park J (Dove Medical Press, 2023)
Donwe Choi,1 Keon-Hyung Lee,2 Jongsun Park3 1Department of Public Administration, Hanyang University, Seoul, Republic of Korea; 2Askew School of Public Administration and Policy, Florida State University, Tallahassee, FL, USA; 3Department of Public Administration, Gachon University, Seongnam-si, Republic of KoreaCorrespondence: Jongsun Park, Department of Public Administration, Gachon University, 1342, Seongnam-daero, Sujeong-gu, Vision Towel, #501, Seongnam-si, Gyeonggi-do, Republic of Korea, Email pjs751101@gachon.ac.krPurpose: Despite the unprecedented challenges caused by the COVID-19 pandemic, nonprofit organizations (NPOs) continued providing services, thereby contributing to overcoming the pandemic. What enabled NPOs to sustain their service provision during this global emergency? This study attempts to answer this question by focusing on one of the essential pillars supporting the operation of NPOs: volunteers. More specifically, we aim to investigate how person-organization (P-O) fit and generation, particularly the Millennial generation, are related to engagement in voluntary activities during the COVID-19 pandemic.Methods: We collected data through an online survey conducted in March 2021. This US national survey was completed by 2307 respondents, yielding the US Census balanced data regarding gender, age, race, education, and income. To analyze the data, we employed the two-stage Heckman selection model.Results: Relying on P-O fit theory and generational theory, the study identifies what led existing volunteers to continue engaging in volunteer activities at their NPO during the COVID-19 pandemic despite the risks. We found that P-O fit mattered in volunteers' decision to continue engaging. In addition, our study uncovered that when existing volunteers were Millennials, the relationship between P-O fit and engagement in voluntary activities strengthened during the pandemic.Conclusion: This study contributes to expanding the explanatory power of the P-O fit theory by testing it in an emergency and extends the generational theory by clarifying under what conditions Millennials (aka Generation Me) transform themselves into Generation We. In addition, linking NPO management and emergency management, this study provides NPO managers with practical implications for securing reliable volunteers who will sustain the capacity of the NPO in a crisis.Keywords: person-organization fit, millennials, existing volunteers, nonprofit organization, COVID-19 pandemic, emergency management